Pengaruh Kemampuan Kerja dan Kompensasi Terhadap Kinerja Pegawai Direktorat Bea dan Cukai Kemenkeu RI - Adila, Mohamad; Sabariah, Etika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effect of work ability and compensation on employee performance at the Directorate of Communication and User Guidance, Directorate General of Customs and Excise, Ministry of Finance of the Republic of Indonesia. Work ability and compensation are important factors in supporting employee performance to improve the effectiveness of service and supervision of the agency. The research method used is quantitative with a survey approach. The sample in this study was 43 employees selected through saturated sampling techniques. The data collection technique used a questionnaire, and data analysis used validity tests, reliability tests, classical assumption tests, hypothesis tests, and determination tests with the help of SPSS software. It is known that the t-value of Variable X1 is 4.735 which is greater than the t-table of 1.684, so there is a positive influence between X1 and Y, the sig value is 0.000 0.05, so the influence is significant. The calculated t value of X2 is 1.868 1.684, there is an influence between X2 and Y, the sig value of X2 is 0.069 0.05, X2 has a significant influence on performance, the f test sig value is 0.001 0.05 and the calculated f value is 83.780 2.84, that Ho is rejected and H1 is accepted, meaning there is a significant influence of variables X1 and X2 simultaneously on performance. The determination value is 0.807 or equal to 80.7%, meaning that variables X1 and X2 simultaneously have an effect on Y of 80.7%. While the remaining (100% - 80.7% = 0.193 variables are not accurate. Where the correlation level at 80.7% can be stated to have a strong correlation. The independent variables in this study are work ability (X₁) and compensation (X₂), while the dependent variable is employee performance (Y). The results of the study show that work ability and compensation partially and simultaneously have a positive and significant effect on employee performance. This finding indicates that increasing work ability and providing appropriate compensation can encourage an increase in overall employee performance.